Investigation of matrix nullity for the second order discrete nonlocal boundary value problem - Paukštaitė, Gailė; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2013)
In this paper we investigate the relation between the matrix nullity of the second order discrete boundary value problem and nonlocal boundary conditions. The obtained classiﬁcation and examples are also presented.